Aphid secondary symbionts do not affect prey attractiveness to two species of predatory lady beetles. - Jennifer L Kovacs; Candice Wolf; Dené Voisin; Seth Wolf (PLoS ONE)
Heritable symbionts have been found to mediate interactions between host species and their natural enemies in a variety of organisms. Aphids, their facultative symbionts, and their potential fitness effects have been particularly well-studied. For example, the aphid facultative symbiont Regiella can protect its host from infection from a fungal pathogen, and aphids with Hamiltonella are less likely to be parasitized by parasitic wasps. Recent work has also found there to be negative fitness effects for the larvae of two species of aphidophagous lady beetles that consumed aphids with facultative symbionts. In both species, larvae that consumed aphids with secondary symbionts were significantly less likely to survive to adulthood. In this study we tested whether adult Harmonia axyridis and Hippodamia convergens lady beetles avoided aphids with symbionts in a series of choice experiments. Adults of both lady beetle species were as likely to choose aphids with symbionts as those without, despite the potential negative fitness effects associated with consuming aphids with facultative symbionts. This may suggest that under natural conditions aphid secondary symbionts are not a significant source of selection for predatory lady beetles.